The Boer goat. I. Origin, adaptability, performance testing, reproduction and milk production - Casey, N.H.; Niekerk, W.A. van (Elsevier, 1988)
Boer goats evolved in southern Africa from indigenous African and introduced European stock. Breed standard of the Boer goat breeder's association stipulate colour to be white with red head and blaze, pigmented skin and good, functional conformation. Boer goats are hardy, graze a wide spectrum of plants, grasses and shrubs, effectively combating bush encroachment, have low water turnover rates and low internal parasites infestation. Does are early breeders, polyoestrous and may be synchronised with intravaginal progestogen or PMSG. A 70 percent kidding rate is reported with AI. Anaplasma ovis infection of does, transmitted transplacentally to the foetus causes abortion and neo-natal mortalities. Milk yield averages range from 1.5 to 2.5 kg/day with 43 g/kg protein and 77 g/kg fat content. Libido and semen quality of bucks varies seasonally. Performance testing aims to measure dam's characteristics pre and post weaning, feed efficiency of kids under standardised conditions, and qualitative and quantitative carcass evaluation of sire's progeny. The future of Boer goats lies in performance testing for economically important traits.